2018
DOI: 10.1186/s12902-018-0265-z
|View full text |Cite
|
Sign up to set email alerts
|

IL-10/STAT3 is reduced in childhood obesity with hypertriglyceridemia and is related to triglyceride level in diet-induced obese rats

Abstract: BackgroundThe prevalence of childhood obesity and obesity-related metabolic disorder such as dyslipidemia has sharply increased in the past few decades. Chronic low-grade inflammation is associated with the development of comorbidities and poor prognosis in obesity. This study aims to evaluate interleukin-10 (IL-10) in childhood obesity with hypertriglyceridemia.MethodWe evaluated IL-10 and signal transducer and activator of transcription 3 (STAT3) mRNA expression in adipose tissue (AT) as well as serum IL-10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 40 publications
0
28
1
2
Order By: Relevance
“…This CpG site has recently been characterized as an LEP interaction region (chr7: 127,854,840-127,881,330). Also based on ENCODE data, cg15758240 is in the vicinity of a number of transcription factor binding sites, including YY1 (−99 bp), CEBPB (−144 bp), USF1 (−164 bp), STAT3 (−184 bp), and GATA2 (−204 bp), which has been previously linked to obesity [36][37][38][39][40], suggesting that cg15758240 is located within a genomic region relevant for both fat accretion and transcriptional regulation activity. Hence, we herein add to the current evidence that the harmful effects of maternal hyperglycemia on offspring adiposity and obesity risk is likely to include epigenetic dysregulation of the leptin gene pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This CpG site has recently been characterized as an LEP interaction region (chr7: 127,854,840-127,881,330). Also based on ENCODE data, cg15758240 is in the vicinity of a number of transcription factor binding sites, including YY1 (−99 bp), CEBPB (−144 bp), USF1 (−164 bp), STAT3 (−184 bp), and GATA2 (−204 bp), which has been previously linked to obesity [36][37][38][39][40], suggesting that cg15758240 is located within a genomic region relevant for both fat accretion and transcriptional regulation activity. Hence, we herein add to the current evidence that the harmful effects of maternal hyperglycemia on offspring adiposity and obesity risk is likely to include epigenetic dysregulation of the leptin gene pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Large scale genomic studies in recent years have furthered our understanding of lncRNAs as functional adipogenic regulators [ 69 ]. IL-10 , an anti-inflammatory cytokine is known to contribute to childhood obesity [ 70 , 71 ], and Liu et al found that IL-10 and the downstream JAK-STAT pathway were down-regulated in obese children with hypertriglyceridemia and in HFD obese rats [ 72 ]. This, indicated a protective effect of IL-10 on lipid metabolic disorders, especially hypertriglyceridemia.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, while STAT3 mRNA expression in adipose tissue is positively correlated with IL-10 and adiponectin expression, it is negatively correlated with triglycerides levels. Therefore, IL-10/JAK-STAT3 pathway activity is decreased due to obesity-related hypertriglyceridemia (Liu et al 2018). PI3K/Akt contributes to hypoxic stressinduced TLR4 expression through the regulation of HIF-1 activation (Kim et al 2012).…”
Section: Uncoupled Respiration and Hypoxiamentioning
confidence: 99%